Anywhere out of the world : The work of Bruce Chatwin - Chatwin, Jonathan (Book collections on Project MUSE., 2012)
Aimed at both the academic and the general reader. There is a large component of entirely new material that will ensure its appeal to those currently working on Chatwin in a research context. The biographical insights and narrative structure will attract the interested Chatwin reader who is keen to discover more about his literary approach.